Determinants of Academic Performance of Chemistry in Secondary School Education in Kenya - Malala, Getrude (JOOUST, 2022)
Academic performance of Chemistry in the Kenya Certificate of Secondary Education exams is lagging both in Bondo Sub County and in Kenya. Despite the interventions by the Ministry of Education such as in-servicing Science teachers through Strengthening of Mathematics and Sciences in Secondary Education (SMASSE) project and review of the syllabus, there has not been much significant improvement. The purpose of this study was to determine the effect of selected determinants on academic performance of Chemistry subject in secondary schools in Bondo Sub County. The study objectives were to; determine the effect of the learners’ attitude on academic performance of Chemistry; establish the teachers’ perception towards the learners’ ability and attitude on academic performance of Chemistry; examine the effect of teaching and learning methodologies on academic performance of Chemistry and assess the role of teaching and learning resources on academic performance of Chemistry in secondary schools in Bondo Sub County. Constructivism theory of the learning process by Jean Piaget was adopted to link it the conceptual framework. The study adopted a correlation research design. The population comprised of the 328 teachers, 4273 student candidates and 1 Quality assurance officer in the Sub County. Stratified sampling, purposive sampling and simple random sampling were the techniques used to obtain samples out of the population. Instruments of data collection were questionnaire, interviews and document analysis. Reliability of instruments was checked by test retest method in a pilot study in 10% of the population outside the actual study population, and the reliability coefficient of 0.53 was achieved. Face, content and construct validity was ascertained by university experts in Planning and Economics of Education. Quantitative data was analyzed with aid of Statistical Package for Social Sciences (SPSS), version 25.0 generating both inferential and descriptive statistics as correlation coefficients, frequency counts, chi square tests, averages and percentages. Qualitative data was analyzed continuously using content and thematic issues, presented by narrations and verbatim quotations, in line with the study objectives. A Pearson correlation co-efficient value of r = 0.078 was established which was a positive correlation between attitude and academic performance in the subject. A Levene’s test was done to test for the sample variance in group means as given by teachers and heads of science departments on student attitude. The p-value was 0.487 ˃ 0.05(a) at 95% confidence interval, hence the variance was not significantly different. P-value for teacher perception was 0.203 ˃ 0.05, in that perception and academic performance were independent of each other. For teaching and learning resources, p = 0.005, ˂0.05, which showed a significant effect of resources on performance. Teaching methodologies played a role in shaping academic performance of the subject. The study concluded that academic performance of Chemistry is defined by effect of student attitude, teacher perception, teaching methodologies teaching and learning resources. The study recommends that education stakeholders including the school principals should endeavor to enhance development programs for teachers of Chemistry such as workshops for training on current issues and trends in methodology so as to build on relevant skills and seal any loopholes which have had an impact on the performance of the subject both in internal and national exams. The findings of the study might be useful to education policy makers, education planners and education stakeholders in making crucial decisions on improving performance in Chemistry and science subjects as a whole.